Production and Perception of Agricultural Reuse in a Rural Community - Arruda, Valmir Cristiano Marques; Cirilo, José Almir; Silva, Vicente de Paulo; Tavares, Rosângela Gomes; Sales Santos, André Felipe de Melo; Ferreira de Queiroz, Alessandro Pelópidas (Revista Geama, 2017)
There is a growing competition among the various sectors of society in the world for the use of water where agriculture stands out as a major consumer. Since it is carried out in a controlled manner, irrigation with effluents from a Sewage Treatment Plant (STP) is a very attractive practice, as it allows a greater supply of water for nobler purposes. This work had the general objective of evaluating the perception of a rural community in the municipality of Pesqueira, Pernambuco, Brasil, in terms of consumption and production of products cultivated with the practice of agricultural reuse. The local population showed acceptance for the cultivation and consumption of products through agricultural reuse, above all, with reliable information on the appropriate quality of the effluents used for irrigation. In the estimated data, the same community had a potential of production of corn, beans and cotton in the order of 19.8 tons, 3.4 tons and 7.7 tons respectively, with the use of treated sewage in irrigation.